Self-initiated expatriates generation Y personality traits and challenges organizations face to recruit them - Sabatelli, Alessandra (2017)
The goal of this dissertation is to expand our understanding about generation Y, more specifically, self-initiated expatriated (SIE) - people who spontaneously decide to go abroad and look for new challenges. Those people present a 'large but untapped pool of skilled international workforce' (Ceric & Crawford, 2016, p.137) with a high potential impact in terms of business and local growth. Therefore, the purpose was to analyse different personality traits and understand how they affect individuals in their job perspective. In order to respond to this question, a field study was conducted and data was collected from a convenience sample of 366 adults where the majority were postgraduate students with an average age of 25 years who have at least experienced studying abroad. The results of the conducted analysis can be summed up in the finding that it didn’t exist a significant connection between personality traits of Generation Y SIE’s and organizational characteristics. In praxis that means that companies do not appeal individuals with a certain personality of this sample by projecting a certain image and, therefore, an individual approach seems to be more appropriate than group targeting.